Development of a Long-Term Athlete Development Model for Long Jump Training Using the IRSA Jumping Exercise Method - Ulia, Irsa Irhamatul; Dwi, Dicky Reva Apriana Sanga (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Based on the findings, the researcher feels it is necessary to improve and enhance long jump techniques during the train-to-train stage (boys aged 12–16 and girls aged 11–15), as this is a period of rapid physical development. At this stage, the researcher can design a training program that is safe and minimizes the risk of injury, especially when using weight training, in order to achieve more optimal training results. Purpose: 1) To analyze the training model process of long jump based on LTAD using the IJE method at the train-to-train stage. 2) To analyze the feasibility of the long jump training model based on LTAD using the IJE method in improving long jump performance. 3) To analyze the effectiveness of the long jump training model based on LTAD using the IJE method in enhancing long jump performance at the train-to-train stage. Methods: This study employs the Research and Development (R&D) method. Results and discussioin: Based on the test results using SPSS 26 for Windows, the data were found to be normally distributed and homogeneously varied. The post-test t-test results indicated a positive effect of the long jump training model on long jump skills among students at SMA Negeri 01 Ciwaru. Conclusion and Implications: Based on the results of the research conducted, it can be concluded that the long jump training model based on Long-Term Athlete Development using the IRSA Jumping Exercise method is feasible to be implemented in the training process. This is supported by various test results indicating that the data are normally distributed and valid. This study provides two implications. First, theoretically, the implementation of this training model can enhance students' interest and motivation in participating in long jump training. Second, practically, this model can serve as an alternative or variation in training programs used by coaches to improve athletes' performance. Limitation and recommendation: For coaches, it is recommended to use the long jump training model as a strategy to enhance athletes' performance. For athletes, this model can serve as motivation and provide a new training experience. Meanwhile, for future researchers, these results can be further developed and used as a reference for subsequent studies.